Study on the Reliability of Capacitor Charging Factor Method in Design Solar Test Simulator Panel Surya - Howard Sifo; Amani Darma Tarigan (Yayasan Sinergi Multidimensi Kreatif, 2024)
This study aims to examine the reliability of the capacitor charging factor method in the design of Solar Test Simulator for Solar Panels. The equipment used is the I-V Tracer, which functions to read the current and voltage characteristic values of the Solar Panels. The value readings on the Solar Panel are greatly influenced by the surrounding environmental conditions and aim to evaluate whether the performance of the panel is in accordance with the available datasheet. The method used to obtain maximum performance data is to perform a short circuit on the output of the solar panel. The data is recorded through a capacitor charging system, where variations in capacitor values are used to determine the optimal component size to display the characteristic curve of the Solar Panel. The final results of the study show that capacitive loads can display the shape of current and voltage curves well through capacitor charging factor monitoring. Tracing the voltage variation in the solar cell and the calculation of the charging current on the capacitor shows that the current generated is relatively small. The 3300 μF capacitor was chosen because it was able to display a curve shape that matched the simulation in the PSIM program. The use of MOSFETs results in real-time charging of capacitors with fast readings in milliseconds.